NIR induced modulation of the red emission from erbium ions for selective lanthanide imaging - Stefan Krause; Mads Koerstz M; Riikka Arppe-Tabbara; Tero Soukka; Tom Vosch (IOP PUBLISHING LTD, 2022)
Upon direct excitation with green light (522 nm), Er3+ ion doped nanoparticles feature a number of radiative and non-radiative decay pathways, leading to distinct and sharp emission lines in the visible and near-infrared (NIR) range. Here we apply, in addition to continuous 522 nm irradiation, a modulated NIR irradiation (1143 nm) to actively control and modulate the red emission intensity (around 650 nm). The modulation of red Er3+ ion emission at a chosen frequency allows us to reconstruct fluorescence images from the Fourier transform amplitude at this particular frequency. Since only the emission from the Er3+ ion is modulated, it allows to selectively recover the lanthanide specific signal, removing any non-modulated auto-fluorescence or background emission resulting from the continuous 522 nm excitation. The modulated emission of specific lanthanides can open up new detection opportunities for selective signal recovery.